DIFFERENCES IN LIPOPROTEIN(A) BY RACE, ETHNICITY, AND ATHEROSCLEROTIC CARDIOVASCULAR DISEASE RISK - Ramzi Dudum, MD MPH; Qiwen Huang, MS; Xiaowei(Sherry) Yan, PhD; Powell Jose, MD; Sumeet Singh Brar, MD; Ashish Sarraju, MD; Fatima Rodriguez, MD MPH (American Journal of Preventive Cardiology, 2023)
Therapeutic Area: ASCVD/CVD Risk Factors Background: Lipoprotein(a) [Lp(a)] is a causal risk factor for atherosclerotic cardiovascular disease (ASCVD). Despite practice guidelines recommending routine Lp(a) testing, uptake of screening has been low and variable. We sought to understand differences in Lp(a) testing and levels by race, ethnicity, and ASCVD risk across a large, integrated healthcare system. Methods: We conducted a retrospective cohort study of patients from a large California healthcare system from 2010 to 2021. Eligible individuals were ≥18 years old, with ≥2 primary care visits, and complete race and ethnicity data who underwent Lp(a) testing. Baseline variables were extracted prior to Lp(a) testing. Race/ethnicity was self-reported and stratified as follows: Non-Hispanic White, Non-Hispanic Black, Hispanic (Mexican, Puerto Rican, Other), Non-Hispanic Asian (Asian Indian, Chinese, Filipino, Japanese, Korean, Vietnamese, Other). T-tests were used to test differences among groups for normally distributed data, Wilcoxon tests for skewed data, and chi-square test for categorical data. Results: Among 1,484,410 patients who met the inclusion criteria, 13,689 (0.9%) underwent Lp(a) testing—mean age 54.6±13.8y, 49% female, 59% Non-Hispanic (NH) White. Average Lp(a) values differed significantly by race and ethnicity ranging from 55mg/dL ±63.3 among NH-Asian participants to 99.8mg/dL ±95.3 for NH-Black individuals. 37.3% of tested patients had Lp(a) levels above 50mg/dL with significant variation among subgroups, ranging from 30.7% of Mexican patients to 62.6% of NH Black patients. Estimated ASCVD risk and clinical ASCVD prevalence varied among tested patients. Asian Indian individuals had the lowest overall risk and NH-Black individuals had the highest overall risk (Panel A). There was an increasing trend of elevated Lp(a) by ASCVD risk—40.6% of those with ≥20% 10-Year ASCVD risk and 43.1% of those with a history of ASCVD across had Lp(a) ≥50mg/dL, compared with 36.2% of those with <5% 10-Year ASCVD risk. Within ASCVD risk groups, elevated Lp(a) differed significantly among race and ethnicity groups. (Panel B). Conclusions: Our study demonstrated that less than 1% of patients underwent Lp(a) testing. Of those tested, Lp(a) levels were elevated and heterogeneous among different race and ethnicity groups. The prevalence of elevated Lp(a) increases with increasing ASCVD risk, with significant variation in race and ethnicity groups.